A study on a factors that influence employees motivation at Pejabat Daerah dan Tanah Temerloh / Nur Hafizah Mahmud - Mahmud, Nur Hafizah (2014)
The title of the research is "A Study on a Factors That Influence Employee Motivation at pejabat Daerah Dan Tanah Temerloh". The purpose of the study is to identify to determine the level of work motivation among workers to identify which factors that most influence on work motivation in, and to identify whether is there any difference of motivation level between difference ranges of age among workers at PDT Temerloh. This study is conducted at Temerloh, Pahang and 50 respondents have been used in the study. A questionnaire has been used as the main medium to collect the data. SPSS version 21.0 is used to analyze all the data collected. It is crucial to the employee to determine the degree of motivation of their workers and the drivers that can boost their motivation in order to keep their employees stays on the right track and to achieve the organization's objective. Based on the finding, it shows that the employees at Pejabat Daerah Dan Tanah Temerloh are motivated by the three variables which is, individual attributes, job characteristic and also organizational factors.